Tri‐functional unit groups contained polyurethane composites with excellent antibacterial property and biocompatibility. Issue 15 (13th May 2022) - Wang, Chuyao; Xue, Yunyun; Tian, Hua; Zhao, Zihao; Shen, Shuyang; Fang, Lifeng; Cui, Ronglu; Han, Jun; Zhu, Baoku
Abstract: As biomaterials, it is essential for polyurethane (PU) to have excellent antibacterial activity and biocompatibility at the same time. Herein, quaternary ammonium groups, sulfonic groups, and alkyl groups simultaneously introduced hyperbranched poly(amidoamine) (HPA‐QSA) was synthesized, which was further used to blend with PU and prepared as films. HPA‐QSA/PU blend films showed strong antibacterial activity to kill more than 99.99% of both Gram‐positive and Gram‐negative bacteria due to the quaternary ammonium groups and long alkyl groups, as well as good biocompatibility through protein‐resistance, cytotoxicity, hemolysis assays under the combined action of cations and anions. Moreover, they exhibited stable antibacterial activity and low cytotoxicity in aquatic solutions. Overall, HPA‐QSA/PU films prepared by facile blending process exhibit great promise as low‐cost, effective antibacterial, good biocompatible materials, indicating an appealing prospect in biomedical fields. Abstract :